2007
DOI: 10.3892/ijo.31.6.1415
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of differentially sulphated bovine kidney- and porcine intestine-derived heparan sulphate on breast carcinoma cellular behaviour

Abstract: Abstract. Heparan sulphate is a sulphated glycosaminoglycan and is able to bind to and regulate the activity of many growth and signalling factors. We have previously shown that its expression is correlated with tumour grade and cell proliferation in breast phyllodes tumours. In this study, we examined the use of heparan sulphate as a biomarker of invasive ductal carcinoma and the effects of differentially sulphated heparan species on breast cancer cell behaviour. Immunohistochemistry using the 10E4 monoclonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…However, to date, the precise structure of the heparan sulfate epitope recognised by the antibody is still unclear. Treatment of cultured cells and embryos with chlorate, a competitive inhibitor of glycosaminoglycan sulfation, resulted in decreased staining by this antibody, suggesting that sulfate groups are present in the 10E4 epitope 14 20. Furthermore, N-desulfation has been reported to destroy the epitope 35.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, to date, the precise structure of the heparan sulfate epitope recognised by the antibody is still unclear. Treatment of cultured cells and embryos with chlorate, a competitive inhibitor of glycosaminoglycan sulfation, resulted in decreased staining by this antibody, suggesting that sulfate groups are present in the 10E4 epitope 14 20. Furthermore, N-desulfation has been reported to destroy the epitope 35.…”
Section: Discussionmentioning
confidence: 97%
“…We have previously shown that heparan sulfate is overexpressed in breast invasive ductal carcinoma and phyllodes tumours, and that differential heparan sulfation patterns are important in regulating breast cancer cellular behaviour 19 20. Structural changes in heparan sulfate during malignant transformation of human colon adenoma to carcinoma have been shown to alter its binding to FGF-2, which is essential for cell proliferation 21 22.…”
mentioning
confidence: 99%
“…Interestingly, two in vitro studies on breast cancer cell lines show that lower HS sulfation patterns decrease cell migration (Guo et al, 2007) and inhibit fibroblast growth factor (FGF)-2 interactions (Delehedde et al, 1996), which inhibited growth. However, in studying the FGF-2/HS-proteogycan interactions, Delehedde and coworkers (1996) also found that decreasing the HS sulfation was not exclusively inhibitory and was, in fact, a growth promoter, within certain limitations, for one of the two breast cancer cell lines studied.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have examined the influence various GAGs on breast cancer cell lines, including the regulation of FGF response to HS chains (Delehedde et al, 1996;Nurcombe et al, 2000), the ability of heparin and low molecular weight heparins to inhibit metastisis (Mellor et al, 2007), increases in motility on HA exposure (Herrera-Gayol and Jothy, 2001), and the inhibitory effect of lowering HS sulfation (Delehedde et al, 1996;Guo et al, 2007). Breast cancer cell lines were also found to secrete factors, which unregulated HA production in other cell lines (Corte et al, 2006).…”
mentioning
confidence: 99%
“…In breast cancer, changes in glycosaminoglycan and proteoglycan expression on the cell surface and in the ECM allow tumor cells to proliferate, gain the ability to invade surrounding tissues, metastasize to distant organs and induce angiogenesis [18,19]. This mini-review focuses on the current clinical use and future potential therapeutic applications of HSPGs in breast cancer treatment.…”
Section: Introductionmentioning
confidence: 98%